Traffic and Granular Flow '15 2016
DOI: 10.1007/978-3-319-33482-0_38
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Pedestrian Evacuation Movement on a Swaying Ship

Abstract: With the advance in living standard, cruise travel has been rapidly expanding around the world in recent years. The transportation of passengers in water has also made a rapid development. It is expected that ships will be more and more widely used. Unfortunately, ship disasters occurred in these years caused serious losses. It raised the concern on effectiveness of passenger evacuation on ships. The present study thus focuses on pedestrian evacuation features on ships. On ships, passenger movements are affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…30). Variations of this model have been used to analyze escape patterns from a building in low visibility conditions [224,215], to assess evacuation plans in skyscrapers [228,229], ships [230] and aircraft [231]. In relation to crowd control, they have also been used to analyze how to mitigate avalanches in the Hajj religious gathering in Saudi Arabia [227,232], in the Notting Hill Carnival in London [233] or, along with mobility models for other transport media, to study evacuation of cities and populated areas in case of natural disasters such as flooding [234,235,236].…”
Section: Pedestrian Movementmentioning
confidence: 99%
“…30). Variations of this model have been used to analyze escape patterns from a building in low visibility conditions [224,215], to assess evacuation plans in skyscrapers [228,229], ships [230] and aircraft [231]. In relation to crowd control, they have also been used to analyze how to mitigate avalanches in the Hajj religious gathering in Saudi Arabia [227,232], in the Notting Hill Carnival in London [233] or, along with mobility models for other transport media, to study evacuation of cities and populated areas in case of natural disasters such as flooding [234,235,236].…”
Section: Pedestrian Movementmentioning
confidence: 99%
“…City University of Hong Kong established a mathematical model to analyse the characteristics of human walking under the action of ship sway. It was concluded that the parallel component of the inertial force of the ship's sway motion affects a person's walking speed in the direction of their advance, which is manifested first as acceleration and then as deceleration (Chen et al, 2016). The German Lloyd's Register of Shipping proposed a model for personnel speed reduction (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…However, the data and parameters specified in the guideline are based on civil building evacuations, and do not take into account the effects on human behaviour of ship movement or family group behaviour, and rarely provide an effective management strategy (Chen et al, 2018(Chen et al, , 2015IMO, 2016;Lee et al, 2003). Compared with the land-based evacuation, evacuating people from crowded passenger ships is a complex and difficult task.…”
Section: Introductionmentioning
confidence: 99%